Study on Development of Learning Media - Muhammad Ediyani; Ulfi Hayati; Salwa Salwa; Samsul Samsul; Nursiah Nursiah; M. Bahriza Fauzi (Budapest International Research and Critics University, 2020)
The development of science and technology is increasingly encouraging renewal efforts in the use of technological outcomes in the teaching and learning process. The teachers are required to be able to use the tools that can be provided by the school, and it is also possible that the tools are in accordance with the development and demands of the times. The teachers can at least use inexpensive and unpretentious tools but is a necessity in the effort to achieve the expected learning goals. The development of instructional media is a plan to develop existing media or intermediary tools in order to improve the quality of information delivery in the teaching-learning process. Development activities learning media in broad outline must go through three major steps namely planning, production and penialian activities.